2015
DOI: 10.1111/add.12875
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of acamprosate and naltrexone in the treatment of alcohol dependence, Europe versus the rest of the world: a meta‐analysis

Abstract: Both acamprosate and naltrexone appear to reduce the risk of individuals returning to drinking alcohol in those who are alcohol-dependent. The country in which a randomized control trial (RCT) for the efficacy of acamprosate and naltrexone is completed does not appear to explain the variance in trial outcomes for returning to drinking alcohol or discontinuing drinking due to adverse effects. However, the country in which the RCT of acamprosate are completed may be important for explaining the variance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 58 publications
2
66
0
6
Order By: Relevance
“…Acamprosate has low oral bioavailability (approximately 11%), is not protein bound, and is not metabolised by the liver, being excreted unchanged in urine [13]. The evidence base includes three recent systematic reviews and metaanalyses [4,6,15] …”
Section: Acamprosatementioning
confidence: 99%
See 1 more Smart Citation
“…Acamprosate has low oral bioavailability (approximately 11%), is not protein bound, and is not metabolised by the liver, being excreted unchanged in urine [13]. The evidence base includes three recent systematic reviews and metaanalyses [4,6,15] …”
Section: Acamprosatementioning
confidence: 99%
“…It is subject to significant first pass metabolism, creating the primary active metabolite 6-beta-naltrexol, which has a half-life of 13 hours [39], the levels of which correlate with adverse events [40]. A substantial evidence base includes systematic reviews and meta-analyses, which demonstrate a significant effect for naltrexone over placebo on relapse rates in heavy drinking (RR 0.83; 95% CI:0.75 to 0.91) [4], and on relapse to any drinking at 3 months (RR = 0.92, 95% CI = 0.86-1.00) [15].…”
Section: Oral Naltrexonementioning
confidence: 99%
“…It has been shown that naltrexone significantly reduces the number of drinking days and the level of alcohol craving [8], with a number needed to treat to prevent a relapse into heavy drinking of 9 [9]. Comparably, the anticraving drug, acamprosate, has been shown to reduce the risk of relapse into any drinking [10], with a number needed to treat to prevent a relapse of 8 [9]. In clinical practice, naltrexone or acamprosate are both considered firstchoice pharmacological treatments, and are prescribed with similar frequencies [5,6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Comparably, the anticraving drug, acamprosate, has been shown to reduce the risk of relapse into any drinking [10], with a number needed to treat to prevent a relapse of 8 [9]. In clinical practice, naltrexone or acamprosate are both considered firstchoice pharmacological treatments, and are prescribed with similar frequencies [5,6,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation